COMPUTER MODELING IN THE DEVELOPMENT OF ARTIFICIAL VENTRICLES OF HEART - L. V. Belyaev; A. V. Zhdanov (Вестник трансплантологии и искусственных органов)
In article modern researches of processes of development of artificial ventricles of heart are described. Advanta- ges of application computer (CAD/CAE) technologies are shown by development of artificial ventricles of heart. The systems developed with application of the given technologies are submitted.